Chrysanthemum embryo development is negatively affected by a novel ERF transcription factor, CmERF12. (28th August 2021) - Xu, Sujuan; Hou, Huizhong; Wu, Ze; Zhao, Jingya; Zhang, Fengjiao; Teng, Renda; Chen, Fadi; Teng, Nianjun
Abstract: Embryo abortion often occurs during distant hybridization events. Apetala 2/ethylene-responsive factor (AP2/ERF) proteins are key transcription factor (TF) regulators of plant development and stress resistance, but their roles in hybrid embryo development are poorly understood. In this study, we isolated a novel AP2/ERF TF, CmERF12, from chrysanthemum and show that it adversely affects embryo development during distant hybridization. Transcriptome and real-time quantitative PCR demonstrate that CmERF12 is expressed at significantly higher levels in aborted ovaries compared with normal ones. CmERF12 localizes to the cell nucleus and contains a conserved EAR motif that mediates its transcription repressor function in yeast and plant cells. We generated artificial microRNA (amiR) CmERF12 transgenic lines of Chrysanthemum morifolium var. 'Yuhualuoying' and conducted distant hybridization with the wild-type tetraploid, Chrysanthemum nankingense, and found that CmERF12 -knock down significantly promoted embryo development and increased the seed-setting rates during hybridization. The expression of various genes related to embryo development was up-regulated in developing ovaries from the cross between female amiR- CmERF12 C. morifolium var. 'Yuhualuoying'× male C. nankingense . Furthermore, CmERF12 directly interacted with CmSUF4, which is known to affect flower development and embryogenesis, and significantly reduced its ability to activate its target gene CmEC1 ( EGG CELL1 ). Our study provides a novel method to overcome barriers to distant hybridization in plants and reveals the mechanism by which CmERF12 negatively affects chrysanthemum embryo development. Abstract : Knock down of CmERF12 in chrysanthemum reduces its negative regulation of CmSUF4 during embryo development and leads to increased seed-setting rate during hybridization.